The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsami.9b14920
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer HfTeSe4: A Promising Two-Dimensional Photovoltaic Material for Solar Cells with High Efficiency

Abstract: Currently, atomically thin materials with high photovoltaic performance are urgently needed for applications in solar cells. Herein, by using first-principles calculations, we propose an excellent two-dimensional photovoltaic material, monolayer HfTeSe4, which can be exfoliated feasibly from its layered bulk. It behaves in the semiconductor character with a moderate direct gap of 1.48 eV and exhibits remarkable absorbance coefficient of ∼105 cm–1 in the visible-light region. Meanwhile, monolayer HfTeSe4 shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 66 publications
2
35
1
Order By: Relevance
“…16 d. In addition, the heterojunctions exhibited a remarkable absorption of sunlight and an enhancement of charge separation behavior due to the type-II band alignment. Utilizing pure 2D ternary compounds, Yang et al [ 210 ] reported a highly efficient solar cell based on monolayer HfTeSe 4 . The simulation outcomes from first-principles calculations indicated that the solar cell exhibited an extraordinary absorbance coefficient of up to 10 5 cm −1 in the visible band, as shown in Fig.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 d. In addition, the heterojunctions exhibited a remarkable absorption of sunlight and an enhancement of charge separation behavior due to the type-II band alignment. Utilizing pure 2D ternary compounds, Yang et al [ 210 ] reported a highly efficient solar cell based on monolayer HfTeSe 4 . The simulation outcomes from first-principles calculations indicated that the solar cell exhibited an extraordinary absorbance coefficient of up to 10 5 cm −1 in the visible band, as shown in Fig.…”
Section: Applicationsmentioning
confidence: 99%
“…h Power conversion efficiency of the HfTeSe 4 /Bi 2 WO 6 heterostructure-based solar cell with and without a 2% tensile strain. Adapted with permission from [ 210 ]. Copyright 2019, American Chemical Society …”
Section: Applicationsmentioning
confidence: 99%
“…With different compositions and crystal structures, these 2D materials differ from each other in properties, offering wide range of material choices for diverse functionalities, including electronics, optoelectronics, sensors, energy conversion, and storage. [ 14–21 …”
Section: Introductionmentioning
confidence: 99%
“…Second-order responses require inversion symmetry breaking and this is satisfied by most topological materials, which has led to discoveries such as Hall effects [12][13][14] in time-reversal invariant systems, and advances in generating non-reciprocal currents [15][16][17][18]. Among the latter, photo-currents are intimately related to the Hilbert space topology and underlie photovoltaic devices [5,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], with potential applications in solar cells, energy harvesting and terahertz devices [37][38][39][40][41][42].…”
mentioning
confidence: 99%